2019
DOI: 10.1038/s41401-019-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes inhibits corneal epithelial cell migration and tight junction formation in mice and human via increasing ROS and impairing Akt signaling

Abstract: Corneal wounds usually heal quickly; but diabetic patients have more fragile corneas and experience delayed and painful healing. In the present study, we compared the healing capacity of corneal epithelial cells (CECs) between normal and diabetic conditions and the potential mechanisms. Primary murine CEC derived from wild-type and diabetic (db/db) mice, as well as primary human CEC were prepared. Human CEC were exposed to high glucose (30 mM) to mimic diabetic conditions. Cell migration and proliferation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…[23][24][25][26][27][28][29] A recent study reported a decrease in TEER in human corneal epithelial cells exposed to 30 mM glucose. 30 Our data are in agreement with this report 30 and additionally demonstrate that corneal epithelial barrier function can also be compromised by moderately high glucose (15 mM). Furthermore, our results also show that high glucose compromises human conjunctival epithelial cell barrier function too.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29] A recent study reported a decrease in TEER in human corneal epithelial cells exposed to 30 mM glucose. 30 Our data are in agreement with this report 30 and additionally demonstrate that corneal epithelial barrier function can also be compromised by moderately high glucose (15 mM). Furthermore, our results also show that high glucose compromises human conjunctival epithelial cell barrier function too.…”
Section: Discussionsupporting
confidence: 92%
“…A literature survey reveals that the effect of high glucose exposure on corneal epithelial cell migration is equivocal with studies reporting a delay, an augmentation, or no change. 30 – 32 Variables such as the use of SV40, telomerase-immortalized, or primary cell types; inclusion/exclusion of serum; and variable epidermal growth factor (EGF) concentrations used in these studies likely contribute to the reported equivocal effect of high glucose exposure on corneal epithelial cell migration. However, our data demonstrate that high glucose exposure does not significantly affect the migration of corneal or conjunctival epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia in diabetes is associated with compromised tissue repair and regeneration in diabetes. Human patients with diabetes often develop oculopathy (29)(30)(31)(32)(33)(34), and db/db mice have previously been used for oculopathy research. Following our published protocol of alkaline-induced ocular injury in mice (13), we found that db/db mice subjected to alkaline-induced ocular injury develop compromised reepithelialization, as measured by sustained fluorescein staining (Fig.…”
Section: Compromised Corneal Wound Healing In Db/db Mice Is Amelioratmentioning
confidence: 99%
“…Additionally, both epithelial and endothelial TJs are disrupted in salivary glands of patients with Sjögren's syndrome (SS) as well as model mice, contributing to salivary hyposecretion (Zhang et al , 2016; Cong et al , 2018). Moreover, TJs are reportedly damaged in other diabetes complications (Jiang et al , 2019; Bu et al , 2020). Cldn1 is upregulated in streptozotocin‐induced mice podocytes, which contributes to the pathogenesis of albuminuria (Hasegawa et al , 2013).…”
Section: Introductionmentioning
confidence: 99%